Genetic Alterations in Intervertebral Disc Disease - Martirosyan, Nikolay L.; Patel, Arpan A.; Carotenuto, Alessandro; Kalani, M. Yashar S.; Belykh, Evgenii; Walker, Corey T.; Preul, Mark C.; Theodore, Nicholas (Frontiers in Surgery, 2016)
Background Intervertebral disc degeneration (IVDD) is considered a multifactorial disease that is influenced by both environmental and genetic factors. The last two decades of research strongly demonstrate that genetic factors contribute about 75% of the IVDD etiology. Recent total genome sequencing studies have shed light on the various single-nucleotide polymorphisms (SNPs) that are associated with IVDD. Aim This review presents comprehensive and updated information about the diversity of genetic factors in the inflammatory, degradative, homeostatic, and structural systems involved in the IVDD. An organized collection of information is provided regarding genetic polymorphisms that have been identified to influence the risk of developing IVDD. Understanding the proteins and signaling systems involved in IVDD can lead to improved understanding and targeting of therapeutics. Materials and methods An electronic literature search was performed using the National Library of Medicine for publications using the keywords genetics of IVDD, lumbar disc degeneration, degenerative disc disease, polymorphisms, SNPs, and disc disease. The articles were then screened based on inclusion criteria that included topics that covered the correlation of SNPs with developing IVDD. Sixty-five articles were identified as containing relevant information. Articles were excluded if they investigated lower back pain or just disc herniation without an analysis of disc degeneration. This study focuses on the chronic degeneration of IVDs. Results Various genes were identified to contain SNPs that influenced the risk of developing IVDD. Among these are genes contributing to structural proteins, such as COL1A1, COL9A3, COL9A3, COL11A1, and COL11A2, ACAN, and CHST3. Furthermore, various SNPs found in the vitamin-D receptor gene are also associated with IVDD. SNPs related to inflammatory cytokine imbalance are associated with IVDD, although some effects are limited by sex and certain populations. SNPs in genes that code for extracellular matrix-degrading enzymes, such as MMP-1, MMP-2, MMP-3, MMP-9, MMP-14, ADAMTS-4, and ADAMTS-5 are also associated with IVDD. Apoptosis-mediating genes, such as caspase 9 gene (CASP9), TRAIL, and death receptor 4 (DR4), as well as those for growth factors, such as growth differentiation factor 5 and VEGF, are identified to have polymorphisms that influence the risk of developing IVDD. Conclusion Within the last 10 years, countless new SNPs have been identified in genes previously unknown to be associated with IVDD. Furthermore, the last decade has also revealed new SNPs identified in genes already known to be involved with increased risk of developing IVDD. Improved understanding of the numerous genetic variants behind various pathophysiological elements of IVDD could help advance personalized care and pharmacotherapeutic strategies for patients suffering from IVDD in the future.